Livelihood, cash transfer, and graduation approaches: How do they compare in terms of cost, impact, and targeting? - Sulaiman, Munshi (International Food Policy Research Institute, 2018)
Chapter 8 provides a comparative analysis of 48 graduation, livelihood, and cash transfer programs. Using income and consumption as the primary metrics of impact and focusing on long-term outcomes, the author assesses the sustainability of impact of these programs and compares both costs and impacts across the three types of approaches.